Appointing Constitutional Court Justices with Statesman Qualification through Transparent Selection Mechanism - Satriawan, Iwan; Erianto , Hanifa (Universitas Lampung, 2024)
There is an unclear definition regarding the qualification of a statesman in the candidacy of Constitutional Court Justices. In addition, no assessment is used to search for those who qualify as statesmen. This study aims to determine the nature and characteristics of statesmen as an indication of the selection mechanism of Indonesian Constitutional Court Justices and evaluate whether the selection mechanism may produce justice with statesman qualification. The research method is normative and empirical legal research, which uses philosophical, historical, conceptual, and statute approaches. The result shows that the concept and nature of statesmanship as a requirement for Constitutional Court Justices is based on the Republic of Indonesia's Constitution and the Constitutional Court Law, which states that Constitutional Court Justices must meet the requirements such as integrity and impeccable personality, fair; and statesman who control the Constitution and state administration. However, the recruitment procedure is excessively more political and unstandardized. Therefore, the current mechanism for selecting Constitutional Court Justices may not generate Justices with statesman-like behavior. The research recommends that in the future, the selection mechanism of the Constitutional Court Justices needs to be reconstructed to produce Justices with statesman qualifications by having a more transparent procedure.